Enhancing Reading Comprehension Through a "Newsinlevels.com" Website as an English Learning Media - Nurhalyza Nabila Putri Setiawan; Moh. Nur Arifin; Selinistia Hidayani (English Education, Linguistics, and Literature Journal, 2025)
‘Digital technology enables the use of websites as an effective medium for learning.’. The research aims to examine the use of newsinlevels.com website as a learning media to enhance reading comprehension skill of descriptive text. The researcher used a quasi-experimental research design with pre-test, post-test and observation as the instruments of collecting data. The researcher used 80 tenth grade students at School of Serang City in 10.3 and 10.2 as the research sample from the total population of 585 tenth grade students. The researcher used T-Test calculation analysis with SPSS. The results of this research show that there has been a significant improvement in students' reading comprehension using the newsinlevels.com website. Based on the results of the research, researcher obtained an average pre-test score of 57.525 and post-test score of 83.075 in the experimental class. Meanwhile, the average pre-test score was 57.5 and post-test score was 72.95 in the control class. it can be seen that the experimental class is better than the control class.But based on the results of hypothesis decision are shown in the p significant U Test results is (0.099), with a significant value (0.05 or 5 %) or (0.099 > 0.05) . It can be concluded, that Ho is accepted, Ha is rejected, this means that use newsinlevels.com website to enhance reading comprehension isn’t effective or refers to the result namely between experiment class and control class isn’t different.